2019
DOI: 10.4028/www.scientific.net/msf.970.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrode Degradation on Properties of Small-Scale Resistance Spot Welded Joints of E110 Alloy

Abstract: Effect of electrode degradation on stability of nugget formation during small-scale resistance spot welding is presented in this paper. Production of spacer grids for nuclear fuel assemblies made of E110 zirconium alloy cells of 0.25 mm thickness was studied. The following degradation processes took place in the electrodes as they wore. Roughness of the tip surface was gradually reduced to the values of the welded cells. The semispherical tips were severely deformed during the initial period of their operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In addition, no pitting and cavitation phenomena in the non-contact area of the carbon imprint were observed in the continuous welding process. The regression model to quantify the relationship between electrode diameter and weld number is given as follows, DE=-0.000017N 2 +0.021N+5.03 (Adj R 2 =0.9855) (14) where DE is electrode diameter. When the number of welds increases from 0 to 176, the electrode diameter increases, and its value is 7.02mm.…”
Section: Changes In Welding Properties With the Increasing Number Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no pitting and cavitation phenomena in the non-contact area of the carbon imprint were observed in the continuous welding process. The regression model to quantify the relationship between electrode diameter and weld number is given as follows, DE=-0.000017N 2 +0.021N+5.03 (Adj R 2 =0.9855) (14) where DE is electrode diameter. When the number of welds increases from 0 to 176, the electrode diameter increases, and its value is 7.02mm.…”
Section: Changes In Welding Properties With the Increasing Number Of ...mentioning
confidence: 99%
“…In this case, they are prone to deterioration, especially when the coated metal sheets are welded [13]. It is discovered that the deterioration of the electrode has an unfavourable effect on the welding quality of the welded joint when the coated or uncoated metal sheets are continuously welded [14]. The standard for electrode life assessment is the number of welds that can be performed repeatedly until the critical acceptable nugget size is impossible to achieve [15].…”
Section: Introductionmentioning
confidence: 99%
“…For titanium alloys, very few recommended SSRSW parameters have been published to date (Table 1), all of which assume the use of typical current pro les of capacitor-based power sources [3][4][5][6] or rectangular-shaped pulses of conventional inverter ones [7][8][9][10][11]. At the same time, some advanced power sources enable to preset almost any algorithms of unipolar pulses with amplitudes of up to several kiloamperes and durations of tens of milliseconds [12][13][14][15][16][17], allowing to improve the quality of the SSRSW joints [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding contact resistance, Chen et al [ 10 ] showed a coating designed as a barrier to prevent the electrodes from alloying with the Zn coating and causing degradation by pitting or erosion, reducing the variations in the contact resistance. Other studies have shown the importance of keeping the geometry of the electrodes constant to reduce variations in the diameter of the active face of the electrodes, either due to excess dirt or mushrooming [ 11 , 12 , 13 , 14 , 15 , 16 ]. In the same way, the contact resistance between metals (R4) has a great importance in the different research that has been carried out; i.e., different authors have focused their studies on the influence that the gap between sheets has on the final quality of the welding point [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%